Fishes of Afghanistan; a revised and updated annotated checklist - Çiçek, Erdoğan; Fricke, Ronald; Eagderi, Soheil; Sungur, Sevil; Coad, Brian W; Hamdard, Mohammad Hamid (Zootaxa, 2023)
The current status of the ichthyofauna of Afghanistan is revised, and an updated checklist is presented. The confirmed fishes of Afghanistan comprise 121 species belonging to 11 orders, 22 families, and 68 genera. Among these, 18 species (14.9%) are alien, and 7 species (5.8%) are considered endemic to Afghanistan. The orders with the largest numbers of species in the ichthyofauna of Afghanistan are Cypriniformes (88 species), followed by Siluriformes (14 species), Anabantiformes (4 species), Acipenseriformes, Salmoniformes, and Cyprinodontiformes (3 species in each). At the family level, Cyprinidae have the greatest number of species (36 species; 29.8% of the total species), followed by Nemacheilidae (22 species), Leuciscidae (12 species), Danionidae (8 species), and Sisoridae (6 species). A total of 48 species previously reported from Afghanistan have been excluded from the checklist, either in the present study or in previous studies. According to the IUCN Red List criteria, among 121 listed fish species, 19 (15.7%) are in the threatened categories, with 4 (3.3%) CR, 6 (5.0%) EN, and 9 (7.4%) VU. Of the total number of taxa assessed, 5.0% (6 species) are NT and 51.2% (62 species) are LC. A total of 29 species are (24.0%) Not Evaluated (NE) and 5 species (4.1%) are classified as DD.